Effects of saddle angle on heavy intensity time trial cycling: Implications of the UCI rule 1.3.014 - Caddy, O.; Timmis, M. A.; Gordon, D. (Journal of Science and Cycling, 2016)
The UCI dictates that during sanctioned events, the saddle of the bicycle may be at angle of no more than 3° of forward rotation, so as to prevent performance advantages (Rule 1.3.014). This research investigates the effect on performance when rotating the saddle beyond the mandated angle during a laboratory 4km time trial (TT). Eleven competitive male cyclists (age 26±6 (mean±SD) yrs, height 179.2±6.7 cm, body mass 72.5±6.7 kg; V?O2max 70.9±8.6 ml·kg-1·min-1) completed laboratory 4km TTs using saddle angles of 0°, 3° and 6°. Completion time and mean power were recorded, in addition to lower appendage kinematics, crank torque kinetics and cardiorespiratory responses. There were no significant changes in TT time, power output, cardiorespiratory variables or crank torque kinetics as a function of saddle angle (P>0.05). There were significant effects on minimum and maximum hip angle and the horizontal displacement of the greater trochanter (P<0.05). At 6° the maximum hip angle and forward displacement of the greater trochanter was greater compared to 0° and 3°. Minimum hip angle was greater at 6° than 3° (P<0.05). In conclusion, contravening UCI rule 1.3.014 by using a saddle angle beyond 3° does not result in performance advantages during a laboratory 4 km. However, tilting the saddle does appear to cause a forward displacement of the pelvis leading to an opening of the hip angle at the top and bottom of the pedal stroke.